Study Skills for Psychology Students / A Practical Guide - Collins Sylvie C; Kneale Pauline E (Arnold, 2001)
This book will help you breeze through your degree. Preface, Acknowledgements, Where are the Skills in Psychology, Maximizing Free Time, Library Electronic Resources, Effective Reading, Making Effective Notes, Thinking, Constructing An Argument, Effective Essay Skills, Citations and References and Sources, Listening and Interviewing, Discussion, Oral Presentations, Writing Practical Reports, Abstracts and Executive Summaries, Dissertations and Final-year Research Projects, Ethics, Reviewing a Book, Posters and Stands, Revision Skills, Examinations, Try This Crossword and Quiz Answers, Study Skills: A Mini-Bibliography, Index.